Kemahiran Membaca Bahasa Arab Tingkat Mutaqaddimin serta Metode dan Strategi Pembelajarannya - Rappe, Rappe (Shaut al Arabiyyah, 2020)
This research discusses the methods and strategies of learning to read especially for mutaqaddimin. Mutaqaddimin is the level where students can already read well and fluently.In this level, the concept of learning focusses aspects of understanding the content of reading as well as the ability to explore it. Reading for mutaqaddimin is activity of learning that can be done independently. So, students can learn in inside or outside the classroom.In learning to read, students are asked to find the main ideas and supporting ideas of the reading. And then recounted it by using grammar or qawaid that student have known. The students must inform it by using their own language so others can understand it well. Every learning needs method and strategies for increasing students interest in studying. And also, make them easy to understand the material. In this case, a teacher have the right to choose a better method and strategies in studying including learning of read. In this research, there are some method and strategies that teacher can use in studying. This research obtaian the data of method and strategies from some jurnals. Researcher read the jurnal well and deeply, then make categorization and choose some importand information in oerder to put in this research